Using iterative fragment assembly and progressive sequence truncation to facilitate phasing and crystal structure determination of distantly related proteins. Issue 5 (1st May 2016) - Wang, Yan; Virtanen, Jouko; Xue, Zhidong; Tesmer, John J. G.; Zhang, Yang
Abstract : An automated pipeline, I‐TASSER‐MR, has been developed to facilitate structure determination using molecular repacement (MR) for samples for which only distantly related structures are available in the Protein Data Bank. By combining iterative fragmental structure‐assembly simulations and progressive trimming of poorly modeled regions, the pipeline improves the success rate of MR. Abstract : Molecular replacement (MR) often requires templates with high homology to solve the phase problem in X‐ray crystallography. I‐TASSER‐MR has been developed to test whether the success rate for structure determination of distant‐homology proteins could be improved by a combination of iterative fragmental structure‐assembly simulations with progressive sequence truncation designed to trim regions with high variation. The pipeline was tested on two independent protein sets consisting of 61 proteins from CASP8 and 100 high‐resolution proteins from the PDB. After excluding homologous templates, I‐TASSER generated full‐length models with an average TM‐score of 0.773, which is 12% higher than the best threading templates. Using these as search models, I‐TASSER‐MR found correct MR solutions for 95 of 161 targets as judged by having a TFZ of >8 or with the final structure closer to the native than the initial search models. The success rate was 16% higher than when using the best threading templates. I‐TASSER‐MR was also applied to 14 protein targets from structure genomics centers. Seven of these were successfully solved by I‐TASSER‐MR . These results confirm that advanced structure assembly and progressive structural editing can significantly improve the success rate of MR for targets with distant homology to proteins of known structure.